2005
DOI: 10.1002/ijc.20882
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism of hybrid liposomes‐induced apoptosis in human tumor cells

Abstract: Hybrid liposomes can be prepared by simply ultrasonicating a mixture of vesicular and micellar molecules in a buffer solution. The physical properties of these liposomes, such as size, membrane fluidity, phase transition temperature and hydrophobicity can be controlled by changing the composition. Hybrid liposomes composed of dimyristoylphosphatidylcholine and polyoxyethylene (10) dodecyl ether were found to inhibit the growth of human promyelocytic leukemia (HL-60) cells without using any drugs. Induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 22 publications
1
46
0
1
Order By: Relevance
“…16,17 Hybrid liposomes being more fluid as compared with DMPC liposomes showed strong inhibitory effects on the growth of human colon cancer (WiDr) cells 16 and human leukemia cells. 12 The strong inhibitory effects on the growth of HCT116 cells should be closely related to the membrane fluidity of HL-n.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Hybrid liposomes being more fluid as compared with DMPC liposomes showed strong inhibitory effects on the growth of human colon cancer (WiDr) cells 16 and human leukemia cells. 12 The strong inhibitory effects on the growth of HCT116 cells should be closely related to the membrane fluidity of HL-n.…”
Section: Dovepressmentioning
confidence: 99%
“…It has been already elucidated that hybrid liposomes induce apoptosis in various tumor cells, with activations of caspases-3, -8, and -9, and reduction of mitochondria membrane potential. 8,[11][12][13]16 HL-n could probably fuse and accumulate into HCT116 cells, and induce apoptosis through activation of caspase cascades.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of HL made of DMPC and polyoxyethylene (n) dodecyl ethers (C 12 (EO) n ) on the in vitro [7][8][9] and in vivo [9][10][11][12] development of lymphoma cells, and clinical applications [12] without drugs have already been reported. In chemotherapy for HER2-negative breast cancer, invasive suppression and the apoptotic induction of breast cancer cell are important treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…5) With respect to the role of Ca 2ϩ in inhibition of cellular proliferation, it has been reported that Ca 2ϩ imported into the cytoplasm of mammalian cells could lead to a programmed cell death "apoptosis" through several signalling pathways. 6,7) However, the mechanistic details of tumor-specific growth inhibition effects of Ca On the other hand, we have investigated the membrane targeted chemotherapy with hybrid liposomes 8,9) composed of phospholipids and nonionic surfactants for tumor cells in vitro, [10][11][12][13][14][15] in vivo, 15,16) and in clinical applications. 16,17) Significantly, the denaturation of cell membranes by hybrid liposomes could lead to apoptosis in tumor cells without any drugs.…”
mentioning
confidence: 99%